2012
DOI: 10.1161/strokeaha.111.625442
|View full text |Cite
|
Sign up to set email alerts
|

Variants on Chromosome 9p21.3 Correlated With ANRIL Expression Contribute to Stroke Risk and Recurrence in a Large Prospective Stroke Population

Abstract: Background and Purpose-ANRIL encodes a long antisense noncoding RNA in the INK4 locus. Although ANRIL has been proven to be associated with coronary heart disease, its roles in stroke are inconsistent, and sparse data are available regarding hemorrhagic stroke. Methods-A Chinese case-control study was conducted, comprising 1657 cases (724 atherothrombosis, 466 lacunar infarction, and 462 hemorrhagic strokes) and 1664 controls. Stroke patients were prospectively followed-up for a median of 4.5 (range, 0.1-6.0) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 36 publications
5
65
1
Order By: Relevance
“…For example, single nucleotide polymorphisms (SNPs) in BRD2, which encodes a chromatin-binding protein that recognizes acetylated histones, confer a significant degree of susceptibility to juvenile myoclonic epilepsy [24]. SNPs in the ANRIL/ CDKN2B-AS1 lncRNA gene on chromosome 9p21.3 are risk loci for a number of diseases, including ischemic and hemorrhagic stroke, intracranial aneurysms, plexiform neurofibromas, and Alzheimer disease (AD) [25,26]. By contrast, SNPs can influence miRNA-mediated gene regulation by creating, destroying, or otherwise modifying miRNA response elements in genes associated with nervous systems disease pathophysiology [e.g., AD, Parkinson disease (PD), multiple sclerosis (MS), schizophrenia, and depression] [27][28][29].…”
Section: Gene Mutations and Other Genomic Featuresmentioning
confidence: 99%
“…For example, single nucleotide polymorphisms (SNPs) in BRD2, which encodes a chromatin-binding protein that recognizes acetylated histones, confer a significant degree of susceptibility to juvenile myoclonic epilepsy [24]. SNPs in the ANRIL/ CDKN2B-AS1 lncRNA gene on chromosome 9p21.3 are risk loci for a number of diseases, including ischemic and hemorrhagic stroke, intracranial aneurysms, plexiform neurofibromas, and Alzheimer disease (AD) [25,26]. By contrast, SNPs can influence miRNA-mediated gene regulation by creating, destroying, or otherwise modifying miRNA response elements in genes associated with nervous systems disease pathophysiology [e.g., AD, Parkinson disease (PD), multiple sclerosis (MS), schizophrenia, and depression] [27][28][29].…”
Section: Gene Mutations and Other Genomic Featuresmentioning
confidence: 99%
“…17 Also, the rs10757278 genotypes were linked to differential expression of ANRIL splice variants, MTAP, and CDKN2A genes in CP tissue. 19 Atherosclerosis development and progression may be affected by differential expression of ANRIL splice variants that could interfere with gene expression in many processes, such as proliferation, remodeling of extracellular matrix, and response to inflammation. 20 The aim of this study was to analyze the possible association of 9p21 rs10757278 polymorphism with CP presence in patients with advanced atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous genome-wide studies have shown that common sequence variants on chromosome 9p21 are closely associated with increased risk of atherosclerotic diseases including coronary artery disease (CAD), [1][2][3][4] myocardial infarction [5][6][7] and stroke, [8][9][10] with the single nucleotide polymorphisms (SNPs) rs10757274 and rs10757278…”
Section: Introductionmentioning
confidence: 99%
“…1,11,12 The homozygous GG genotype of rs10757278 is associated with CAD severity, extent and progression in Caucasian populations, 13 and both loci are also significantly associated with ischaemic stroke risk. 9,14 The increased risk of atherosclerosis is mediated via effects on the expression of cyclin-dependent kinase inhibitor 2 A (CDKN2A, also known as INK4/ARF). 9,15,16 Peripheral arterial disease (PAD) is a common form of atherosclerotic disease that has a similar aetiology and pathogenesis to CAD and ischaemic stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation